2018
DOI: 10.3390/ijms19113595
|View full text |Cite
|
Sign up to set email alerts
|

HGF/MET and the Immune System: Relevance for Cancer Immunotherapy

Abstract: An overactivation of hepatocyte growth factor (HGF)/mesenchymal-epithelial transition factor (MET) axis promotes tumorigenesis and tumor progression in various cancer types. Research data recently evidenced that HGF/MET signaling is also involved also in the immune response, mainly modulating dendritic cells functions. In general, the pathway seems to play an immunosuppressive role, thus hypothesizing that it could constitute a mechanism of primary and acquired resistance to cancer immunotherapy. Recently, som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
77
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 92 publications
2
77
0
1
Order By: Relevance
“…Hepatocyte growth factor (HGF) is an activator of mitosis and identical to “scatter factor”, which stimulates epithelial cells to disperse in culture (Stoker et al, 1987; Nakamura, 1989). HGF is also implicated in branching morphogenesis (Zhang and Vande Woude, 2003), tumorigenesis (Zhang et al, 2018), immune cell regulation (Papaccio et al, 2018), neuronal survival (Thompson et al, 2004; Nakano et al, 2017), wound healing (Miyagi et al, 2018), neuronal differentiation, synapse formation and maturation (Matsumoto et al, 2014). There are numerous studies of HGF structure, domains, splice isoforms and diverse functions (Comoglio et al, 2003; Matsumoto et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocyte growth factor (HGF) is an activator of mitosis and identical to “scatter factor”, which stimulates epithelial cells to disperse in culture (Stoker et al, 1987; Nakamura, 1989). HGF is also implicated in branching morphogenesis (Zhang and Vande Woude, 2003), tumorigenesis (Zhang et al, 2018), immune cell regulation (Papaccio et al, 2018), neuronal survival (Thompson et al, 2004; Nakano et al, 2017), wound healing (Miyagi et al, 2018), neuronal differentiation, synapse formation and maturation (Matsumoto et al, 2014). There are numerous studies of HGF structure, domains, splice isoforms and diverse functions (Comoglio et al, 2003; Matsumoto et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…50 MET modulates dendritic cells to play an immunosuppressive role. 51 The reasons why LTBR which is important for homeostasis of dendritic cells, 52 IL1R1 which is important for IL-17 generation, and IL-1 function 53 and CCL19 which enhances Th1 immunity 54 are down regulated are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Using the ProcartaPlexHuman Cytokine/Chemokine/Growth Factor Panel and the ProcartaPlexHuman Immuno-Oncology Checkpoint Panel, we found that patients with lower baseline plasma HGF or IL-8 levels, or a decrease of plasma IL-8, or an increase of plasma TIM-3 or CD152 level at 8 weeks after treatment may bene t more from camrelizumab with apatinib. Recent studies showed that high serum levels of the c-MET ligand HGF correlated with increasing neutrophil counts, which was associated with poor responses to checkpoint blockade therapies (17)(18)(19)(20). IL-8 is secreted by malignant tumor and stroma cells across many different types of tumor, and is a member of the CXC chemokine family identi ed as a chemotactic factor for neutrophils (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%